PERAN UNITED NATIONS WOMEN (UN WOMEN) DALAM MENCIPTAKAN KESETARAN GENDER DI AFGHANISTAN - Anisa Trianjani; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study analyzes the role of UN Women in creating gender equality in Afghanistan. Afghan women have experienced a lot of discrimination, such as not being allowed to leave the house without the assistance of a muhrim or a brother, being restricted from getting an education, and not being allowed to work. Therefore, UN Women is present in Afghanistan to help women regain their rights by carrying out various strategic programs and activities that have been designed by UN Women. This study uses qualitative methods, with data collection techniques using library research methods by collecting data sources from journals, books, and websites. This study uses the perspective of Pluralism and uses the theory of the role of International Organizations. Based on these data, this study succeeded in finding that the role of UN Women in Afghanistan has a role as an Instrument, Arena and Independent Actor. These roles have made a difference in creating gender equality for Afghan women, although there are still problems left behind. Keywords: UN Women, Gender Equality, Afghanistan.